Gift Sharing on Social Media: What Drives It? - Lee, Mira; Kang, Yoon-Hee (Asia Marketing Journal (Online), 2023)
This study examines factors influencing gift sharing on social media. An online survey gathered data from American adults. It investigates how motivations for social media content posting, gift attributes, giver characteristics, and recipient reactions affect gift-sharing behavior. Findings show self-expression motives in content posting drive sharing, while social interaction motives do not. Gifts perceived as experiential and expensive are more likely to be shared. Recipient-centric gifts positively influence gift sharing, while giver-centric gifts hinder sharing. Attitude towards the gift predicts sharing, while appreciation does not. The study enhances understanding of gift sharing on social media and offers marketing insights for leveraging this behavior.